(X-45)*60% =45 + (X-45)*40% 怎么解方程
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 11:49:42
(X-45)*60%=45+(X-45)*40%怎么解方程(X-45)*60%=45+(X-45)*40%怎么解方程(X-45)*60%=45+(X-45)*40%怎么解方程(X-45)*60%=45
(X-45)*60% =45 + (X-45)*40% 怎么解方程
(X-45)*60% =45 + (X-45)*40% 怎么解方程
(X-45)*60% =45 + (X-45)*40% 怎么解方程
(X-45)*60% =45 + (X-45)*40%
0.6(x-45)=45+0.4(x-45)
0.6x-0.6×45=45+0.4x-0.4×45
0.2x=45+27-18
x=270
(X-45)*20%=45
X-45=225
X=270
?
0.6X-27=45+0.4X-18
0.6X-0.4X=23+27
0.2X=50
X=250
(45% x + 15) / x = 60% x怎么解
45X(x+1)=60X 怎么解
45X=60(X-1)
(4/x-5)+(x-3)/(12-x)=(x-45)/(x^2-17x+60)
6.8+60%x=14 x+45%x=11.6 75%x-四分之一x=38
x/45+x/90-x/60=1 解方程
45X=(4-X)*30 X=1.6
45x+10 =50X(x-1)
(X-30)/X=45/100 求X
x-20%x=45+20%x
x/45=(x+30)/60+1 x=270x/45=(x+30)/60+1x=270
45x+15=60x-60
45x-15=60x-60
x/45=x/60-15
x/45=1+(x+30)/60
x/75+x/60=45
X/45=(X+30)/60-1
x/75+x/60=45